First Palestinian Intifada and intergenerational transmission of human capital - Sameh Hallaq (Levy Economics Institute of Bard College, 2020)
This paper attempts to estimate the intergenerational transmission of human capital in Palestine. The main question is whether formal parental education improves their offspring's cognitive skills and school achievements. I use the instrumental variable (IV) method in the estimations to overcome the potential endogeneity of parental education. The main source of variation in parental educational attainment is parents' exposure to the First Palestinian Intifada (1988-93) during their middle- and high school ages. During the First Palestinian Intifada, many school days were lost due to frequent school closures and other restrictions. Furthermore, many young people preferred to search for low-skill employment in Israel, since it provided them with better wages than the local labor market and hardly required any level of educational attainment. This study employs two outcomes, namely the standardized cognitive test scores and school achievements during the academic year 2012/13 for students between grade 5 and grade 9 in West Bank schools. Overall, the results support the hypothesis of a human capital spillover but more so for girls than for boys, where the IV results are often insignificant because of their large standard errors.
Keywords: I20; J62; 330; Intergenerational Mobility; First Intifada